On N-Dimensional Achr-Algebras - Mohammed, Amir A.; Hasan, Abdulhakeem L. (Science Journal of University of Zakho, 2013)
We prove that a homomorphismfrom complete normed algebra A into an n-dimensional normed algebra B is automatically continuous. As a consequence, B is ACHR-algebra.
Keywords: Automatic continuity; Finite-dimension; Homomorphism; Normed algebra